Depression effect of the cold filter plugging point by blending of palm oil, palm stearin, and palm olein biodiesels in petrodiesels - Yuan, Min-Hao; Chen, Yi-Hung; Peng, Siou-Chih; Chen, Lu-Yen; Chang, Ching-Yuan; Santikunaporn, Malee; Assavatesanuphap, Channarong; Lee, Yi-Fa (Frontiers in Energy Research, 2022)
The cold filter plugging point (CFPP) has been widely used to evaluate the low-temperature operability of neat biodiesel and biodiesel–petrodiesel blends in many European and Asian countries. In this study, six kinds of palm biodiesels (palm oil, palm stearin, and palm olein methyl esters in undistilled and distilled forms) in two Taiwanese major petrodiesels (CPC and FPCC) were adopted to examine their CFPP from 100 vol% biodiesel (B100) to 100 vol% diesel (D100 or B0). The results showed that the CFPPs of B2–B12 for CPC and B10–B12 for FPCC were consistently lower than the initial CFPP of D100 from all the palm biodiesel. The most significant depression effect of CFPP was found in B10, where the CFPP of B10 was substantially reduced to about 3–7°C as compared with those of D100 in both petrodiesels. The CFPP of B10 was from −7 to −8°C in CPC and −10 to −13°C in FPCC, where CFPPs of CPC and FPCC neat fuels were −4 and −6°C, respectively. Undistilled palm oil and palm olein biodiesels exhibited stronger depression effect than distilled palm biodiesels at the same level of biodiesel–petrodiesel blends and covered a wider range for the depression effect. Even though the CFPP of palm biodiesels falls outside the limit of Taiwanese B100, the finding revealed that a low blending of B2–B12 of palm biodiesels can result in a better and satisfactory CFPP of biodiesel–petrodiesel admixture that meets the diesel standard CNS 1471.